MOTIVASI DALAM MENINGKATKANKINERJA PEGAWAI DIKANTOR KECAMATAN SEI RAYA KABUPATEN KUBU RAYA - Sindy, Sindy; Yohanes, Yulius; Rupita, Rupita (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
The writing of this research aimed to analyze the motivation on employee performance at the Sungai Raya Sub-District Office, Kubu Raya Regency and to determine the impact of performance motivation on services to the people of Sungai Raya Sub-District, Kubu Raya Regency. The problems found were: The suboptimal employee performance at the Sei Raya Sub-District Office, Kubu Raya Regency, the lack of motivation from the head of the Sungai Raya Sub-District Office to their subordinates so that the performance was ineffective and inefficient and the lack of strategies in improving the employee performance at the Sungai Raya Sub-District Office, Kubu Raya Regency. This research used a descriptive qualitative approach. Data collection techniques that were required consisted of primary data and secondary data, while field research aimed at obtaining data, and the implementation was in the form of interviews with several informants who were considered knowledgeable with the problem. The research results were analyzed qualitatively. According to Gomes (2001: 180), work motivation factors consisted of two parts, namely individual factors and organizational factors. Individual factors were classified as needs, goals, attitudes, and abilities. While those classified as organizational factors consisted of; payment of salaries/wages, job security, employee relations, supervision, praises, and the job itself.Â Â Keywords: Strategy, Work Motivation, Employees, Public Service.